2011
DOI: 10.1155/2011/972759
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Hepascore as a Predictor of Liver Fibrosis in Patients with Chronic Hepatitis C Infection

Abstract: Introduction. Liver biopsy is an invasive determinator for hepatic fibrosis. Serum biomarkers can probably be used as an alternative to liver biopsy in assessment of the degree of fibrosis in patients with chronic Hepatitis C. Method. Eighty patients with chronic Hepatitis C were included in the study using simple nonrandom sampeling metod. After fulfillment of liver biopsy, the patients were categorized according to the METAVIR Scoring system. The Hepascore algorithm is computed based on age, sex, and the ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Recently, several studies were published about estimation of hepatitis stages, using one or more serum biomarkers. Discriminant functions or multivariate analyses demonstrated that approximately 60–90% of patients with chronic hepatitis C were correctly classified as mild hepatitis and severe hepatitis with advanced fibrosis . The usefulness of the discriminant functions was, however, less valuable up to the present time for a few reasons.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Recently, several studies were published about estimation of hepatitis stages, using one or more serum biomarkers. Discriminant functions or multivariate analyses demonstrated that approximately 60–90% of patients with chronic hepatitis C were correctly classified as mild hepatitis and severe hepatitis with advanced fibrosis . The usefulness of the discriminant functions was, however, less valuable up to the present time for a few reasons.…”
Section: Introductionmentioning
confidence: 83%
“…Discriminant functions or multivariate analyses demonstrated that approximately 60-90% of patients with chronic hepatitis C were correctly classified as mild hepatitis and severe hepatitis with advanced fibrosis. [5][6][7][8][9][10][11][12][13][14][15][16] The usefulness of the discriminant functions was, however, less valuable up to the present time for a few reasons. First, these functions were made for the purpose of discrimination of severe hepatic fibrosis from mild fibrosis, and four histological classifications (F1, F2, F3 and F4) were selected in almost of the studies.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, ELF between 9.8-11.3 will likely exclude cirrhosis, as well as lack of fibrosis, deeming a liver biopsy often necessary to establish the degree of fibrosis (44). In contrast, Kalantari et al (34) found higher HA levels in females compared to males, although patients were not stratified by age group or fibrosis stage, both of which were also independent predictors of HA levels. Both HA and the ELF score were lower in patients with sustained response compared to those without sustained response in a cohort of chronic HCV patients treated with pegylated interferon plus ribavirin (35).…”
Section: Methodsmentioning
confidence: 98%
“…It was devised in a cohort of chronic HCV patients [66] and further validated in several studies [67][68][69][70][71][72] . An interesting advantage of Hepascore ® is that it can be totally automated using a single analyzer and only one serum sample [69] .…”
Section: Direct (Or Class ⅰ) Markers Of Liver Fibrosismentioning
confidence: 99%